From Market to State: the adaptability of Peronism facing the neoliberal collapse (Colección, 2017)
Peronism as a political party, has undergone myriad of critical circumstances who forced him to operate adaptive strategies in order to maintain resources, power, influence or ensure his own political survival. The shift to the neoliberal paradigm, under the government of Carlos Menem, and the return to the track of economic heterodoxy, during the first years of Néstor Kirchner administration, have been two of the most drastic adaptive mutations implemented. The first one was addressed by Flavia Burgess and Steven Levitsky through a theoretical model of two levels. The objective of this work is to recover the categories of that conceptual apparatus in order to unravel the determinants of the second.
Keywords: Adaptive capacity; Political parties; Neoliberal policy; Heterodox economy; Peronism